Use of global forests dynamics monitoring database and form recommendations for sustainable management by the Tropical Managed Forest Observatory Network - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The Tropical Managed Forest Observatory Network (TmFO) monitors the dynamics of tropical logged forests around the world to develop new evidence-based logging practices that maintain long-term forest functions for ecosystem functioning and economic viability. TmFO brings new paradigms for management of forests, particularly in the Amazon, demonstrates caveats in selective logging rules to inform sustainable transitions, and creates the basis for collective action on sustainable and profitable forest management over the long term.